Strengthening the Institutional Structure of the Ombudsman of the Republic of Indonesia: The Urgency of Revising Law Number 37 of 2008 from the Perspective of Fiqh Siyasah - Sari, Vidya Nirmala; Holijah, Holijah (Jurnal El-Thawalib, 2026)
This research examines the weakened oversight function of the Ombudsman of the Republic of Indonesia in public service delivery as a consequence of three fundamental deficiencies within Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. First, the absence of executive enforcement authority over the Ombudsman’s recommendations results in its operation merely as a magistrature of influence, unlike its counterparts in developed jurisdictions. Second, the Ombudsman’s institutional position remains ambiguous and marginal within the state structure, as it is neither explicitly nor implicitly regulated in the 1945 Constitution. Third, budgetary and human resource constraints inevitably follow from such limited authority, while maladministration practices continue to rise, totaling 81,432 reports over the past two decades. The findings conclude that institutionally, the Ombudsman functions as a state auxiliary organ and, functionally, as part of the fourth branch of government. However, it currently exercises only a magistrature of influence, necessitating a legal transformation into a magistrature of sanction. From the perspective of fiqih siyasah (Islamic political jurisprudence), strengthening the Ombudsman is imperative, as it aligns with the principle of al-amr bi al-ma’ruf wa al-nahy ‘an al-munkar (commanding right and forbidding wrong), the concept of wilayat al-hisbah (public accountability institution), and the objectives of maqashid al-shariah. The proposed institutional strengthening model through legal revision comprises four simultaneous measures: (1) establishing binding executive authority for recommendations; (2) optimizing preventive and educational functions based on the Fiqh Anti-Maladministration framework; (3) strengthening an integrated complaint reporting system with whistleblower protection; and (4) internalizing fiqih siyasah values (trustworthiness, justice, public interest, accountability) into positive law. This research recommends that the revision of Law Number 37 of 2008 accommodate all four measures concurrently, thereby transforming the Ombudsman into a strong, independent supervisory institution capable of performing the hisbah function within a modern constitutional state.